Conflicts and cooperation in the mountainous Mapuche territory (Argentina) - Renaud Miniconi; Sylvain Guyot (Revue de Géographie Alpine)
Over the past two decades, indigenous issues have become a major concern for different countries all over the world. Argentina is one of these countries, with 600 000 people who recognize themselves as indigenous, representing 1.5% of the nation’s entire population. Nevertheless, these populations are still too often marginalized on a regional scale. This is the case for the Mapuche in the Nahuel Huapi National Park, located in the two provinces of Rio Negro and Neuquén. Even though both international and some national texts rehabilitate essential human rights for these populations, local realities are more contrasted due to regional stakeholders’ divergent interests. In the particular context of Argentina, where a large part of the population faces problems gaining access to land, national parks have emerged as a relevant tool for indigenous peoples to recover their ancestral lands, especially thanks to a new process taking place in these territories: co-management.